Anaerobic Soil Disinfestation as a Tool for Nematode and Weed Management in Organic Sweetpotato - Simardeep Singh; Matthew Cutulle; William Rutter; Phillip A. Wadl; Brian Ward; Churamani Khanal (Agronomy)
Anaerobic soil disinfestation (ASD) is a promising alternative to synthetic chemical-driven pest management methods facilitated by incorporating carbon sources into the soil, tarping the soil with plastic mulch, and irrigating to soil saturation. To evaluate the impact of ASD on southern root-knot nematode [Meloidogyne incognita (Kofoid & White), SRKN] and yellow nutsedge (Cyperus esculentus L.) management in organically grown sweetpotato, greenhouse studies were conducted. The treatments were structured as a factorial of two carbon amendments [chicken manure + molasses (CM + M), and no additional carbon (control)] by 20 sweetpotato genotypes with 4 replications using a randomized complete block design. The results suggest that the microcosms receiving the carbon amendment spent the most time under anaerobic conditions (<200 mvh). Planting of sweetpotato genotypes in CM + M-treated microcosms resulted in 60–90% and 56–92% suppression of soil population and egg reproduction of SRKN as compared to no additional carbon. The application of CM + M reduced overall weed cover by 79% relative to the control. Sweetpotatoes in CM + M-treated microcosms had significantly higher dry above-ground biomass (6.8 g) as compared to the control (3.6 g). The results of this study demonstrated that ASD has the potential to manage nematodes and weeds in organic sweetpotato production systems.